The medial prefrontal cortex as a proposed regulatory structure in the relationship between anxiety and perceived social support: a review - D. A Navarro-Nolasco; D Chi-Castañeda; M. L López-Meraz; L Beltran-Parrazal; C Morgado-Valle (BMC Psychology)
Abstract Perceived social support is recognized as a critical protective factor against the development of mental health disorders. Anxiety disorders are the most common group of mental health disorders and have a substantial impact on individuals' well-being. Despite extensive research on anxiety and perceived social support, a significant gap exists in our understanding of the neural mechanisms linking these two phenomena. While several brain regions, including the amygdala, hippocampus, and insula, have been implicated in anxiety regulation and social support processing, the medial prefrontal cortex (mPFC) emerges as a particularly intriguing structure due to its central role in emotional regulation and social processing. Here, we hypothesize that the mPFC serves as a potential neural substrate mediating the relationship between anxiety and perceived social support. To support our hypothesis, we conducted a literature search in the PubMed database using a systematic Boolean search strategy. In total, 43 articles met our inclusion criteria. The reviewed studies suggest that the mPFC may play an essential role in regulating the effect of perceived social support on anxiety levels. The evidence indicates that individuals with higher levels of perceived social support may exhibit enhanced regulatory control over anxiety-related processes, with the mPFC mediating this effect. Understanding the neural mechanisms that underpin the relationship between anxiety and social support is crucial for devising targeted interventions. Further investigation into mPFC's role as a candidate structure in this domain could provide invaluable insights and aid in the development of new therapeutic strategies for the management of anxiety.